Spatial distribution of cerebral microbleeds reveals heterogeneous pathogenesis in CADASIL - Chen, Ya-Fang; Chen, Chih-Hao; Wu, Wen-Chau; Lee, Bo-Ching; Tsai, Hsin-Hsi; Tang, Sung-Chun (European radiology, 2022)
Objectives Radiological diagnosis of subtypes of cerebral small vessel diseases remains challenging. This study aimed to explore the spatial distribution of cerebral microbleeds (CMBs) in cerebral autosomal dominant arteriopathy with subcortical infarct and leukoencephalopathy (CADASIL) in contrast to cerebral amyloid angiopathy (CAA) in the lobar regions. Methods Thirty-two patients with CADASIL and 33 patients with probable CAA were prospectively and consecutively included. On 3-Tesla susceptibility-weighted magnetic resonance images, CMBs were analyzed for incidence and volume within atlas-based regions of interest, followed by voxel-wise analysis using risk mapping. The distribution of CMBs was correlated with the status of hypertension. Correlation and group differences with a p -value less than 0.05 were considered to be significant. Results As compared with the CAA group, the CADASIL group presents a larger CMB volume in hippocampus/amygdala and white matter (nonparametric analysis of covariance, p = 0.014 and 0.037, respectively), a smaller CMB volume in parietal lobe ( p = 0.038), and a higher incidence in hippocampus/amygdala, white matter, and insula (logistic regression, p = 0.019, 0.024, and 0.30, respectively). As part of the exclusion criteria of probable CAA, thalamus, basal ganglia, and pons exhibit greater CMB volume/incidence in the CADASIL group. In CADASIL patients, hot spots of CMBs are identified in the putamen and posteromedial thalamus; hypertension is associated with larger CMB volumes in insula, basal ganglia, and pons. Conclusions The spatial distribution of CMBs is differentiable between CADASIL and CAA in lobar regions. In CADASIL patients, hypertension has a region-dependent mediating effect on the CMB volume. Key Points • The topological distribution of lobar CMBs is differentiable between CADASIL and CAA. • In CADASIL patients, hypertension mediates CMB volume and the mediation is region dependent. • CMB risk mapping allows for voxel-wise exploration of CMB distribution and reveals hot spots in the putamen and posteromedial thalamus in CADASIL.